Amelioration Potential of Piperine on Cypermethrin-Induced Immunotoxicity in Wistar Rats - Sankar, Palanisamy; Telang, Avinash Gopal (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The aim of the present study was to evaluate the immunemodulatory potential of piperine against cypermethrin-induced immune  dysfunction in a rat model. Thirty rats were divided into five groups of six each. Group I was kept as control and group II was used as  vehicle control. Groups III, IV and V were administered orally with cypermethrin (25 mg/kg, b.wt., per oral), piperine (50 mg/kg, b.wt., per  oral) and both daily for 4 weeks, respectively. Subchronic exposure to cypermethrin significantly reduced body weight, total leukocyte  count, lymphocyte count, serum total protein, serum albumin, serum globulin, antibody titer against sheep red blood cells, and cell mediated immunity. Simultaneous piperine administration restored the changes in the body weight, haematological parameters,  and serum biochemical indices and significantly increased the antibody titer and cell mediated immunity. These results suggest that  simultaneous piperine treatment has restore the number of factors known to be involved in the cypermethrin induced immunotoxicity  which indicates that piperine can be used as a safe and effective therapy for environmental contaminants induced immunotoxicity.
Keywords: Cypermethrin; Immunomodulation; Piperine; Rats